Impact of hybrid education in higher education: a systematic review - Herencia-Escalante, Victor Hugo; Cardenas-Zedano, William Jesús; Etchart-Puza, Jimena Angelica; Rojas Chacaltana, Sergio Arturo (Institute of Advanced Engineering and Science, 2025)
In recent times, educational initiatives such as hybrid education have positioned themselves as important approaches to ensure the continuity of education during a period as complicated as the COVID-19 pandemic. In this context, the objective of this article is to explore the rise and development of hybrid education worldwide in recent years as a viable alternative within higher education institutions, through a systematic review of the literature applying the preferred reporting items for systematic reviews and meta-analyses (PRISMA) method. From this review, it is observed that hybrid education has experienced significant progress during the COVID-19 pandemic, given the transition to virtuality that was experienced and the rise of new digital technologies that prove useful for this approach. At the same time, the interest shown by both students and teachers in adopting this new approach instead of a purely face-to-face or virtual one has become evident, although there are still several challenges to overcome before it can be properly implemented.